Conservation and preservation of philological collections at the Bengkulu state museum - Sigiro, Dewi Suryani; Darubekti, Nurhayati; Samosir, Fransiska Timoria; Valentino, Rahmat Alifin (Jurnal Kajian Informasi dan Perpustakaan, 2026)
Background: The Bengkulu State Museum houses a variety of rare collections that represent the culture of the Bengkulu people. One of the rare collections housed in this museum is the philology collection. The museum conducts conservation and preservation efforts to extend the lifespan of its philological collection materials. Purpose: This study examined the conservation and preservation methods used by the Bengkulu State Museum to protect its philological collection. Methods: The researcher used a descriptive qualitative method. Data was collected through interviews, direct observation, and document analysis. This research was conducted in March 2025. The data analysis had three main steps: coding the data, presenting or organizing the data, and drawing and checking conclusions. Results: Findings indicated that the Museum used three main methods to protect the collection: active preservation, passive preservation, and digital preservation through digitization. Conclusion: The Bengkulu State Museum carries out conservation and preservation activities for its philological collections through active and passive conservation measures. Active conservation activities are also optimized by using organic materials, such as spices, to reduce reliance on chemicals in collection care. Passive conservation includes implementing collection care procedures as outlined in the Collection Care SOP. Digital preservation involves converting the philological collection into a digital format. Implications: The findings highlight the need to enhance funding, facilities, and the availability of qualified experts to support optimal conservation practices. The use of natural materials and collaboration in digital preservation are crucial strategies to address limited resources and ensure the sustainability of collection preservation.